PENDAMPINGAN PEMBUATAN PETA JALUR EVAKUASI BENCANA BERBASIS SIG DI DESA PEMENANG TIMUR, KABUPATEN LOMBOK UTARA - Yunianti, Sri Rahmi (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
East Pemenang Village is one of the tourist destination villages in North Lombok district, with coastal and hilly areas. There are also religious tourism such as the Vanna Sabha Loka Vihara in Jeliman Ireng district and the Jaya Wijaya Vihara in Tebango district (Anwar et al, 2023). However, the 2018 earthquake caused damage to the tourist location. The purpose of the service activity to assist in the preparation of Disaster Evacuation Route Maps using the Geographic Information System (GIS) Application is to compile data and create disaster information media in the form of a map. Information in the maps related to disaster evacuation routes need to be prepared to make it easier for the community and tourists in the East Pemenang Village to know the evacuation routes and assembly points when a disaster are coming. The method used in this activity was FGD with the community and the East Pemenang village officials. The result of this activity is that there is a GIS-based disaster evacuation route map and the community and village officials understand the importance of digital maps in the disaster risk management process.